Catalogue of goods to be sold by publick vendue : on Wednesday the eighteenth day of September 1754, at the house of Mrs. Henrietta Maria Caine, at the Sign of the Fann in Marlborough-Street, Boston - Caine, Henrietta Maria ([publisher not identified], 1754)
Catalog of 283 items to be sold on September 18, 1754 at Henrietta Maria Caine's home.